Association of Perceived Stress with Acute Coronary Syndrome: A Matched Case Control Study - Shah, Prashant; KC, Heera; Parajuli, Surya Bahadur (Journal of College of Medical Sciences-Nepal, 2024)
Background Acute Coronary Syndrome (ACS), a leading cause of morbidity and mortality globally. While traditional risk factors for ACS are well studied, the role of perceived stress remains underexplored in our context. Hence, we aimed to find the association of perceived Stress with Acute Coronary Syndrome. Methods A hospital based case control study, matched with age and gender was conducted at Birat medical College teaching Hospital from 1st July to 28th November2023. Consecutive sampling techniques was employed to enroll 50 cases and 50 controls from the hospital. Data on demographics and risk factors were collected, and the Perceived Stress Scale-10 (PSS-10) was used to measure stress in both groups. Multivariate logistic regression analysis was conducted to determine the independent association of PSS-10 with ACS. Results Perceived stress had no statistical significant association with ACS (P=0.069, OR= 0.918, CI 0.837-1.007) when adjusting for other risk factors. However, hypertension (P=0.004, OR=4.59, CI=1.61-13.09), smoking (P=0.004, OR=8.48, CI=2.09-34.38), and a family history of cardiovascular disease (P=0.028, OR=4.97, CI=1.19-20.75) showed statistically significant associations with ACS, while controlling for other factors. Conclusions The study found higher perceived stress in ACS patients, but it wasn't an independent predictor of ACS. Significant associations with hypertension, smoking, and family history emphasize the need for comprehensive risk factor management in preventing cardiovascular disease.